Pengaruh Sistem Pelaporan, Pengendalian Akuntansi, Dan Kejelasan Sasaran Anggaran Terhadap Akuntabilitas Kinerja Instansi Pemerintah Dengan Kompetensi Aparatur Sebagai Variabel ModerasI (Studi Kasus Pada BPJS Ketenagakerjaan Se-Eks Karesidenan Surakarta - Nisa Ullulfi Nur Azizah; Aris Eddy Sarwono (Jurnal Akuntansi Keuangan dan Bisnis, 2024)
This study aims to analyze the impact of reporting systems, accounting controls, and budget target clarity on the performance accountability of government agencies, with the competency of apparatus as a moderating variable at BPJS Ketenagakerjaan in the former Karesidenan Surakarta region. The research employs a quantitative method. The population consists of BPJS Ketenagakerjaan employees in the former Karesidenan Surakarta region, with a purposive sampling method resulting in a total of 42 respondents. The data used in this study are analyzed using SPSS version 21 software. The study reveals that reporting systems and budget target clarity have a significant positive impact on the performance accountability of government agencies. However, accounting controls have a positive but insignificant impact on performance accountability. The MRA test results show that the competency of apparatus does not function as a moderating variable to strengthen or weaken the relationship between independent and dependent variables.